Exploring the Influence of Growth-Related Conditions on the Antioxidant and Anticholinergic Properties of Pressurized Arctium lappa L. Root Extracts - Enrico Romano; Gloria Domínguez-Rodríguez; Luisa Mannina; Alejandro Cifuentes; Elena Ibáñez (Applied Sciences)
Arctium lappa L., commonly known as burdock, is a biennial plant whose roots are a valuable source of bioactive phenolic compounds with notable health-promoting properties. However, the bioactivity of these compounds is influenced by both extraction parameters and plant growth conditions. This study investigated the combined effect of extraction temperature, land management, and cultivation altitude on the antioxidant and anticholinergic potential of burdock root extracts obtained through pressurized liquid extraction (PLE). Extractions were performed at 50 °C, 100 °C, and 150 °C, with 50 °C being the temperature that best preserved phenolic content and bioactivity. Remarkably, root extracts obtained at 50 °C and collected from an untreated organic field at 150 m altitude yielded higher phenolic levels (42 mg gallic acid/g extract) than conventional solid–liquid extraction (38 mg gallic acid/g extract). A comparative analysis of three ecotypes, including Organic Land Ecotype (OLE) and Spontaneous Land Ecotype (SPLE), both collected at 150 m altitude, and Spontaneous Mountain Ecotype (SPME), collected at 800 m (over sea level), revealed that a higher altitude significantly increased phenolic content and anticholinergic potential. Furthermore, roots from non-weeded soils exhibited superior bioactivity compared to those from weeded areas. These findings underline that the successful obtention of highly bioactive burdock root extracts depends not only on extraction conditions, but also critically on cultivation altitude and land management strategies.